Size and growth of the threadfin bream (Nemipterus japonicus Bloch, 1791) which was caught in the fishing apartment in Kire Waters Central Mamuju - Ibrahim, Ibrahim; Dananjaya, Wayan Kantun; Moka, Wilma Joana (Acta Aquatica: Aquatic Sciences Journal, 2025)
Threadfin bream is a demersal fish that is intensively used by the community because it has high economic value. thereby encouraging increased fishing efforts both in open waters and in areas where fish apartments are installed. Therefore, there is a need for studies of Threadfin bream caught in fish apartments as an effort to maintain their survival. This research aims to analyze the size distribution, length-weight relationship, and condition factors of threadfin bream caught in fish apartments. The research is classified as a survey type with data sources from fishermen's catches carried out in three fish apartments that have been installed for six years in Kire Budong-Budong Village, Central Mamuju Regency. The research results showed that the number of threadfin bream that were observed was 205 fish with a distribution of 46 fish in the first apartment, 67 fish in the second apartment and 92 fish in the third apartment. The length and weight of threadfin bream caught in each apartment were 20.28 ± 2.74 cm and 120.66 ± 37.84 g for the first apartment, 20.16 ± 3.24 cm and 121.52 ± 48, respectively. 44 for the second apartment 20.13 ± 3.15 cm and 120.74 ± 45.85 g for the third apartment. Meanwhile, the growth pattern of threadfin bream for the three fish apartments was negative allometric and the condition factor value ranges from 0.8872 to 1.145.Keywords: Central Mamuju; Condition Factor; Fish Apartment; Growth; Size Distribution; Threadfin Bream